Legal Protection of Stray Animals; A Comparative Study of Pakistan, Malaysia And UK - Rabia Ibrar; Kainat Manzoor; Hina Qayyum; Dr. Nadia Khadam (Indus Journal of Social Sciences, 2025)
Animals being living things possess some rights by virtue of their existence but the rights can be enforced in any state only when they are legally recognized. This becomes problematic when it comes to the legal protection of stray animals. This study critically analyzes the legal status of stray animals in Pakistan in comparison with United Kingdom and Malaysia. Though the amendments have been made from time to time but this research puts a light on the loopholes in the laws of said countries. The main rationale of the research is to highlight that stray animals’ reason of existence is not only to facilitate humans rather they have a complete, independent existence of their own. This has been done using five theoretical frameworks. The research sheds light on the maltreatment of such animals in Pakistan. The reference has also been made to a case law of Pakistan which is a step towards new approach of dealing strays. The research then suggests methods to cope up the issues.